Preparation and Thermal Properties of Poly(phosphazene-aryl ester) Containing Cyclotriphosphazene Structures - Zhao, Zhengping; Ji, Jianbing; Yu, Fengying (Asian Journal of Chemistry, 2014)
Newly aromatic poly(phosphazene-aryl ester) was prepared by polycondensation reaction of synthesized aromatic diols: 1,1,3,5-tetraphenoxy-3,5-bis(4-hydroxyphenoxy) cyclotriphosphazene with terephthaloyl dichloride. The chemical structure of the synthesized diols and polyphenyl esters were characterized by elemental analysis, 1H and 31P NMR and FTIR techniques, whereas their thermal and crystallize properties were determined by DSC, TGA and XRD techniques. Compared to conventional p-oxybenzoyl homopolyester, the poly(phosphazene-aryl ester) shows excellent thermal stability and solubility in polar protic solvents. Poly(phosphazene-aryl ester) shows two thermal degradation in the temperature range 150-600 °C while the monomer, indently its structure, shows the first maximum rate of thermal decomposition temperature around 150-300 °C, which may be due to the decomposition of the P-O-C bond.